La gestión turística municipal y el desarrollo del distrito de cascas, provincia gran chimú- región la libertad 2013-2014 - Albites Mendoza, María Elena (2014)
The present investigation about The Municipal Tourism Management in Tourism Development in the District of Cascas 2013, Province Gran Chimu- Region La Libertad is to determine how the municipal tourism management is manifested in the development of tourism in the district Cascas which is identified and explains the approach of the tourism industry policies, organization and planning of the area of the municipality of Tourism Cascas, the annual operating plan ordinances and participation in tourism related activity Tourist programs and improving the urban beautification Cascas and qualified human resource management likewise the joint work of the local management committee mi Tierra a product with the municipal government explained, the training activities described tour operators, implementation of permanent workshops related to tourism, and participation in tourism events considering that the municipality is the level of government closest to the people and is responsible for enhancing tourism, using planning tools and management for tourism development, that is why in the present study is performed based on the municipal tourism management Cascas District for the purpose of making known their strengths and weaknesses diagnosis.